Effect of Age on Cancer-specific Mortality in Patients With Urothelial Carcinoma of the Urinary Bladder: A Population-based Competing-risks Analysis Across Disease Stages. (December 2020) - Luzzago, Stefano; Knipper, Sophie; Palumbo, Carlotta; Rosiello, Giuseppe; Pecoraro, Angela; Deuker, Marina; Mistretta, Francesco A.; Tian, Zhe; Musi, Gennaro; Montanari, Emanuele; Shariat, Shahrokh F.; Saad, Fred; et al.
Abstract : Objective: The objective of the study is to test the effect of age on cancer-specific mortality (CSM) in patients with urothelial carcinoma of the urinary bladder (UCUB), across all disease stages. Materials and Methods: Within the Surveillance, Epidemiology, and End Results (SEER) registry (2004-2016), we identified 207, 714 patients. Age was categorized as: below 60 versus 60 to 69 versus 70 to 79 versus 80 years and above. Multivariable competing-risks regression (CRR) models were used according to disease stage (low-risk nonmuscle invasive: TaN0M0 low grade, high-risk nonmuscle invasive: Ta high grade or Tis-1N0M0, muscle invasive: T2-3N0M0, regional: T4N0M0/TanyN1-3M0, and metastatic: TanyNanyM1). Results: Overall, 33, 970 (16.4%) versus 52, 173 (25.1%) versus 64, 537 (31.1%) versus 57, 034 (27.4%) patients were below 60 versus 60 to 69 versus 70 to 79 versus 80 years and above, respectively. In multivariable CRR models that focused on low-risk nonmuscle invasive UCUB, advanced age was associated with higher CSM rates (hazard ratio [HR]: 7.04 in patients aged 80 y and above, relative to below 60 y; P <0.001). Moreover, advanced age was also associated with higher CSM rates in high-risk nonmuscle invasive UCUB (HR: 2.77 in patients aged 80 y and above, relative to below 60 y; P <0.001) and in muscle invasive UCUB patients (HR: 1.38 in patients aged 80 y and above, relative to below 60 y; P <0.001). Conversely, lower CSM rates with advanced age were observed in multivariable CRR that focused on regional (HR: 0.91 for patients aged 80 y and above, relative to below 60 y; P =0.02) or metastatic UCUB (HR: 0.75 for patients aged 80 y and above, relative to below 60 y; P <0.001). Conclusions: The direction and the magnitude of the association between advanced age and CSM in UCUB patients changes according to tumor stage. In low-risk nonmuscle invasive, high-risk nonmuscle invasive, and muscle invasive UCUB, more advanced age is associated with higher CSM rates. Conversely, in regional and metastatic UCUB patients, more advanced age is associated with lower CSM rates.